1995
DOI: 10.1111/1523-1747.ep12325522
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 of Keratinocyte Origin Is a Mediator of Melanocyte Dendricity

Abstract: Melanocytes synthesize melanin and transfer it to keratinocytes via dendritic processes. Keratinocytes are known to produce constitutively several factors, including endothelin-1 (ET-1), that together affect melanocyte proliferation, migration, melanogenesis, and dendrite formation. After ultraviolet (UV) irradiation, synthesis and secretion of ET-1 are up-regulated in keratinocytes. Because UV irradiation of skin is known to be associated with increased melanocyte dendricity, and because medium conditioned by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 25 publications
3
119
1
Order By: Relevance
“…In a preliminary in vivo study, we were not able to find any significant differences between melanocytes from the two age groups when stained with dopa, NKI-beteb or S100 (data not shown). Considering the positive correlation between melanin formation and dendricity suggested by previous studies (Hara et al 1995;Nakazawa et al 1993), the findings seem to conflict. However, our findings agree with those of a previous study indicating that adult and neonatal melanocytes respond similarly to melanogenic stimulation by CT and IBMX (Abdel-Malek et al 1994).…”
Section: Melanin Content and Distributioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In a preliminary in vivo study, we were not able to find any significant differences between melanocytes from the two age groups when stained with dopa, NKI-beteb or S100 (data not shown). Considering the positive correlation between melanin formation and dendricity suggested by previous studies (Hara et al 1995;Nakazawa et al 1993), the findings seem to conflict. However, our findings agree with those of a previous study indicating that adult and neonatal melanocytes respond similarly to melanogenic stimulation by CT and IBMX (Abdel-Malek et al 1994).…”
Section: Melanin Content and Distributioncontrasting
confidence: 54%
“…Through dendritic processes, melanocytes transfer melanosomes into neighboring keratinocytes. Accordingly, melanocyte dendricity is a crucial factor in epidermal pigmentation (Hara et al 1995;Mosher et al 1993). This close relationship between melanocyte dendricity and pigmentation in vivo is supported by previous experimental findings showing that dendrite formation by cultured melanocytes correlates very well with melanogenesis (Hara et al 1995;Nakazawa et al 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among keratinocyte-secreted factors, which induce melanocyte activation, we find prostaglandins PGE2 (32), a-MSH and ACTH (33), endothelin-1 (34,35) and NO (20). a-MSH, ACTH and PGE2 activate the cAMP pathway in melanocytes, while NO activates the cGMP-dependent signaling events.…”
Section: Indirect Effects Of Uvmentioning
confidence: 99%
“…In response to hormones and UV irradiation, melanin pigments are synthesized in melanosomes, which are transferred from the tips of melanocyte dendrites to the surrounding keratinocytes to protect against UV damage or carcinogenic effects (Boissy 2003;Okazaki et al 1976;Seiberg 2001). Studies have demonstrated that the dendritic outgrowth of melanocyte/melanoma cells is promoted by UV irradiation, cAMP-elevating agents and growth factors, as well as by the induction of melanogenesis; therefore, dendrites are recognized as a morphological indicator of melanocyte/melanoma cell differentiation (Hara et al 1995;Yoshida et al 2000). We investigated the formation of dendrites in B16 2F2 cells incubated with compound 1.…”
Section: Dendrite Formationmentioning
confidence: 99%